The Effect of Sales Growth, Dividend Policy and Return on Assets on Debt Policy in Property and Real Estate Companies Listed on the Indonesia Stock Exchange in 2013 - 2017 - Rajesh Chashmum; Deepanwita Jagravi; Jayanti Sari (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
The aim of this study was to examine and analyze the effect of Sales Growth, Dividend Policy and Return On Assets simultaneously and partially on Debt Policy in Property and Real Estate companies listed on the Indonesia Stock Exchange for the 2013–2017 period. The data analysis method used was multiple linear regression. The samples used in this study were 13 companies. The results of this study indicate that the variables Sales Growth, Dividend Policy and Return On Assets simultaneously have a significant effect on debt policy. Partially, Sales Growth and Dividend Policy have no significant effect on policy. Only Return On Assets has a significant effect on debt policy in property and real estate companies listed on the Indonesian stock exchange for the 2013-2017 period